Relação entre Fluência e Compreensão Leitora em Escolares com Dificuldades de Aprendizagem - Cunha, Vera Lúcia Orlandi; Martins, Maíra Anelli; Capellini, Simone Aparecida (Instituto de Psicologia, Universidade de Brasília, 2017)
ABSTRACT The capacity to read and comprehending text is essential in our daily life and in the educational context. Considering this aspect the objective of this study was to compare fluency and reading comprehension of students from second to fifth grade of primary school with and without learning difficulties. The eighty students who participated were divided into eight groups: GI to GIV (students without learning difficulties); GV to GVIII (students with learning difficulties). Of the oral reading of a text were measured the time, accuracy, speed and reading comprehension. Statistically significant differences were observed on all these variables indicating inferior performance to the students with learning difficulties. It was found that difficulties in reading fluency interfered with reading comprehension.

RESUMO A capacidade para ler e compreender textos é fundamental tanto em nossa vida diária como no contexto educativo. Considerando esse aspecto, o objetivo deste estudo foi comparar a fluência e a compreensão de leitura de escolares do segundo para o quinto ano do ensino fundamental com e sem dificuldades de aprendizagem. Participaram oitenta escolares divididos em oito grupos: GI a GIV (escolares sem dificuldades de aprendizagem); GV a GVIII (escolares com dificuldades de aprendizagem). Por meio da leitura oral de um texto, foram medidos tempo, exatidão, velocidade e compreensão de leitura. Houve diferenças estatisticamente significativas em todas as variáveis, indicando desempenho inferior para os escolares com dificuldades de aprendizagem. Verificou-se que as dificuldades de fluência de leitura interferiram na compreensão leitora.
Relating between Fluency and Reading Comprehension in Students with Learning Difficulties
Keywords: reading; reading fluency; reading comprehension; reading skills; leitura; fluência de leitura; compreensão da leitura; habilidades para leitura